pengaruh komunikasi internal dan motivasi terhadap kinerja tenaga kependidikan di era new normal covid-19 - juni lius telussa (Widya Komunika, 2021)
“ ABSTRACK In the new normal era, everything changes in various activities, and must adjust accordingly. The magnitude of change is caused by the corona virus which has spread to almost all parts of the world. All areas of the economy have collapsed and are even powerless to face it. Likewise in the world education sector, virus Covid-19 also has the world to education in Indonesia. From Kindergarten level to College level, experience a new pattern of learning and teaching processes. Not only students but also teachers must be able to adapt to new technology. Learning online (online) and offline (outside the network), is a new thing in the learning process of teaching distance. Likewise, the way of communicating between education personnel changes and must adjust to the circumstances so that motivation and performance are maintained. In this study the researcher wanted to know, and had the aim of analyzing and knowing the effect of internal communication and work motivation on the performance of educational staff employees in the new normal era. This research uses explanative research. The population in this study were all educational staff at Candle Tree Junior High School. For data collection techniques, namely through distributing questionnaires or questionnaires, interviews, observation, and documentation as well as school data. As for the data analysis technique, researchers used quantitative methods and adjusted to the results of their research.